Feminism and the Literature of Pramoedya Ananta Toer - Tjong, Cendrawaty (Bina Nusantara University, 2013)
Feminism refers to the social ideological trends that women ask for equal rights as well as the results of ideology when women know the world, the ego, and the sexual relationship in their process of seeking self-liberation. This paper starts with describing the periods in which Indonesian women acknowledged and was associated with western feminism as well as analyzing its period of development. This paper aims at researching the feminism idelology of Pramoedya Ananta Toer, a leading Indonesian writer, including the factors which affect his opinion on women and the expression of his feminism, which is richly displayed throughout his works. The finding of this research shows that in Pramoedya Ananta Toer’s perspective, equality between men and women is manifested in the partnership between men and women, that this partnership is applied in every aspect of lives, which is advanced-throught in Indonesian’s patriarchal society.